Keratoconus, Inflammatory and Epigenetic Biomarkers: An integrative review of the molecular basis and translational perspectives (Research, Society and Development, 2026)
Introduction: Keratoconus (KC) is a multifactorial corneal ectasia in which oxidative stress, chronic low-grade inflammation, and epigenetic alterations contribute to stromal thinning and loss of corneal biomechanical integrity. Inflammatory and epigenetic biomarkers detected in tear film, corneal tissue, and peripheral blood have emerged as promising tools for early diagnosis, risk stratification, and therapeutic monitoring. Objective: To synthesize current evidence on inflammatory and epigenetic biomarkers associated with keratoconus, with emphasis on molecular markers relevant to clinical application and translational research. Methods: An integrative review was conducted using PubMed/MEDLINE, Scopus, Web of Science, and SciELO databases, covering the period from 2000 to 2025. Search terms included “keratoconus”, “biomarkers”, “inflammatory mediators”, “cytokines”, “tear film”, “epigenetics”, “DNA methylation”, and “microRNA”. Original studies and reviews addressing inflammatory or epigenetic molecular biomarkers in keratoconus were included. Results and Discussion: Increased levels of pro-inflammatory cytokines (IL-1β, IL-6, IL-8, TNF-α), matrix metalloproteinases—particularly MMP-9—and oxidative stress mediators were consistently observed in tear film and corneal tissue of keratoconus patients, correlating with disease severity and progression. Systemic markers, such as neutrophil-to-lymphocyte and monocyte-to-HDL ratios, circulating cytokines, and vitamin D levels, suggest a systemic inflammatory and metabolic component. At the epigenetic level, differentially expressed microRNAs and DNA methylation changes in genes related to extracellular matrix remodeling, stress response, and TGF-β signaling have been identified. Conclusion: Keratoconus is an inflammatory-degenerative disease modulated by genetic and epigenetic factors. Inflammatory and epigenetic biomarkers are promising tools for diagnosis and monitoring; however, methodological heterogeneity and limited longitudinal data still restrict their clinical implementation.